UMPSAs compassionate visit programme extends service to Tuaran community - Mimi Rabita, Abd Wahit (UMPSA, 2024)
TUARAN, 1 March 2024 - Concerned about the plight of some families facing difficulties, the management team of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) visited five families in and around Kampung Roun, Serusup, Selupoh, and foster families in Kampung Batangan as part of the ‘Program Ziarah Prihatin UMPSA@Rumah Baiti Jannati’ in conjunction with the ‘Program Kembara Prihatin@Negeri di bawah Bayu 2.0’.